Comparative expression profiling of the Chlamydia trachomatis pmp gene family for clinical and reference strains. - Alexandra Nunes (PLoS ONE, 2007)
Chlamydia trachomatis, an obligate intracellular pathogen, is a leading worldwide cause of ocular and urogenital diseases. Advances have been made in our understanding of the nine-member polymorphic membrane protein (Pmp) gene (pmp) family of C. trachomatis. However, there is only limited information on their biologic role, especially for biological variants (biovar) and clinical strains.We evaluated expression for pmps throughout development for reference strains E/Bour and L2/434, representing different biovars, and for clinical E and L2 strains. Immunoreactivity of patient sera to recombinant (r)Pmps was also determined. All pmps were expressed at two hours. pmpA had the lowest expression but was up-regulated at 12 h for all strains, indicating involvement in reticulate body development. For pmpD, expression peaked at 36 h. Additionally, 57.7% of sera from infected and 0% from uninfected adolescents were reactive to rPmpD (p = 0.001), suggesting a role in immunogenicity. pmpF had the highest expression levels for all clinical strains and L2/434 with differential expression of the pmpFE operon for the same strains. Sera were nonreactive to rPmpF despite immunoreactivity to rMOMP and rPmpD, suggesting that PmpF is not associated with humoral immune responses. pmpFE sequences for clinical strains were identical to those of the respective reference strains. We identified the putative pmpFE promoter, which was, surprisingly, 100% conserved for all strains. Analyses of ribosomal binding sites, RNase E, and hairpin structures suggested complex regulatory mechanism(s) for this >6 Kb operon.The dissimilar expression of the same pmp for different C. trachomatis strains may explain different strain-specific needs and phenotypic distinctions. This is further supported by the differential immunoreactivity to rPmpD and rPmpF of sera from patients infected with different strains. Furthermore, clinical E strains did not correlate with the E reference strain at the gene expression level, reinforcing the need for expansive studies of clinical strains.